Proceedings of the 2011 IEEE National Aerospace and Electronics Conference (NAECON) 2011
DOI: 10.1109/naecon.2011.6183108
|View full text |Cite
|
Sign up to set email alerts
|

Scaling function waveform for effective side-lobe suppression in radar signal

Abstract: Scaling function of generic wavelet is proposed to be the radar waveform of a radar signal. Its shows significant advantage on conventional linear frequency modulated (LFM) or chirp radar waveform in side-lobe compression. To increase the bandwidth of the radar waveform, we further propose a new radar waveform named chirp-Z, which is composed of wavelet packets. The generation of the chirp-Z signal is introduced, and the signal is compared with the chirp radar pulse with the same duration and same bandwidth ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…From the table one can see that the wavelet-based waveforms express a 2 to 4 dB enhancement. This observation validates the simulated results ([7]). …”
supporting
confidence: 92%
See 1 more Smart Citation
“…From the table one can see that the wavelet-based waveforms express a 2 to 4 dB enhancement. This observation validates the simulated results ([7]). …”
supporting
confidence: 92%
“…In the previous study [7], it has been shown the autocorrelation of the scaling function generates very little sidelobes in comparison with the conventional LFM as shown in Figure 3, and the main lobe of that of the wavelet-based waveform is narrower than that of the LFM waveform. The goal of the test is to verify if those two theoretical results are also practically true.…”
Section: A the Wavelet-based Radar Waveformmentioning
confidence: 82%
“…The wavelet-based waveform (WBW) has been studied for suppressing range sidelobes [1]. The study indicates that WBW can suppress sidelobes to noise-like signal.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [15] proposed transmitting single wavelet functions and performing wavelet decomposition at the receiver, instead of using matched filters. In our previous study of WBW [1], we studied in both theory and experiment how WBW can improve the performance in the range detection for static targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation